Wide bandgap semiconductors : growth, processing and applications - Pearton, S. J. (Materials science and process technology series., 2000)
Provides technical applications for key processes such as laser diodes, LEDs, and very high temperature electronic controls on engines. Focuses on on doping, etching, oxidation passivation, growth techniques, etc.